Factors influencing the use of antenatal care in rural West Sumatra, Indonesia - Agus Yenita; Horiuchi Shigeko (BMC, 2012)
Abstract Background Every year, nearly half a million women and girls needlessly die as a result of complications during pregnancy, childbirth or the 6 weeks following delivery. Almost all (99%) of these deaths occur in developing countries. The study aim was to describe the factors related to low visits for antenatal care (ANC) services among pregnant women in Indonesia. Method A total of 145 of 200 married women of reproductive age who were pregnant or had experienced birth responded to the questionnaire about their ANC visits. We developed a questionnaire containing 35 items and four sections. Section one and two included the women's socio demographics, section three about basic knowledge of pregnancy and section four contained two subsections about preferences about midwives and preferences about Traditional Birth Attendant (TBA) and the second subsections were traditional beliefs. Data were collected using a convenience sampling strategy during July and August 2010, from 10 villages in the Tanjung Emas. Multiple regression analysis was used for preference for types of providers. Results Three-quarter of respondents (77.9%) received ANC more than four times. The other 22.1% received ANC less than four times. 59.4% received ANC visits during pregnancy, which was statistically significant compared to multiparous (p = 0.001). Women who were encouraged by their family to receive ANC had statistically significant higher traditional belief scores compared to those who encouraged themselves (p = 0.003). Preference for TBAs was most strongly affected by traditional beliefs (p < 0.001). On the contrary, preference for midwives was negatively correlated with traditional beliefs (p < 0.001). Conclusions Parity was the factor influencing women's receiving less than the recommended four ANC visits during pregnancy. Women who were encouraged by their family to get ANC services had higher traditional beliefs score than women who encouraged themselves. Moreover, traditional beliefs followed by lower income families had the greater influence over preferring TBAs, with the opposite trend for preferring midwives. Increased attention needs to be given to the women; it also very important for exploring women's perceptions about health services that they received.